The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.onc.1208951
|View full text |Cite
|
Sign up to set email alerts
|

TP53INP1 is a novel p73 target gene that induces cell cycle arrest and cell death by modulating p73 transcriptional activity

Abstract: TP53INP1 is an alternatively spliced gene encoding two nuclear protein isoforms (TP53INP1a and TP53INP1b), whose transcription is activated by p53. When overexpressed, both isoforms induce cell cycle arrest in G1 and enhance p53-mediated apoptosis. TP53INP1s also interact with the p53 gene and regulate p53 transcriptional activity. We report here that TP53INP1 expression is induced during experimental acute pancreatitis in p53 À/À mice and in cisplatin-treated p53 À/À mouse embryo fibroblasts (MEFs). We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 39 publications
8
115
0
Order By: Relevance
“…In a search for the mechanism of apoptosis in the absence of p53, we found that EGCG treatment induced the expression of p73 but not p63 and that inactivation of p73 protects cells from EGCG-induced apoptosis. The results of our study are consistent with previous reports that p73 is sufficient to induce apoptosis in cells lacking functional p53 (36)(37)(38). However, there is no notable difference in the expression levels of p73 between SHP-2 WT and mutant cells, although there are remarkable differences in apoptosis and expression of target genes.…”
Section: Discussionsupporting
confidence: 83%
“…In a search for the mechanism of apoptosis in the absence of p53, we found that EGCG treatment induced the expression of p73 but not p63 and that inactivation of p73 protects cells from EGCG-induced apoptosis. The results of our study are consistent with previous reports that p73 is sufficient to induce apoptosis in cells lacking functional p53 (36)(37)(38). However, there is no notable difference in the expression levels of p73 between SHP-2 WT and mutant cells, although there are remarkable differences in apoptosis and expression of target genes.…”
Section: Discussionsupporting
confidence: 83%
“…Further evidence of the proliferative actions of ERa is that the most strongly ERa-downregulated gene was the cell cycle repressor TP53INP1, a downregulation that was opposed by ERb. Increase of TP53INP1 leads to cycle arrest in G 1 and enhanced p53-mediated apoptosis (Tomasini et al, 2005). In addition, several antiproliferative genes (QSCN6, NDRG3, SEPT9, KCTD11 and STK3) are affected by ERb alone, strongly supporting the notion that ERb is antiproliferative and capable of inhibiting or reducing the growth of tumors.…”
Section: Antiproliferative and Antitumorigenic Actions Of Erbmentioning
confidence: 71%
“…Cisplatin is a strong, widely used anti-cancer therapeutic drug that causes DNA damage and programmed cell death and is activated in a p53-independent pathway [35,36] . Here, we have demonstrated that with the treatment of cisplatin, expression levels of cleaved Caspase-3 and PARP were elevated and accompanied by increased migfilin expression.…”
Section: Discussionmentioning
confidence: 99%